Pentamera fonsecae n. sp. a new species of sea cucumber from the Pacific coast of Costa Rica (Holothuroidea: Dendrochirotida: Thyonidae) - Solis-Marin, Francisco Alonso; Alvarado, Juan Jose; Conejeros-Vargas, Carlos Andres; Caballero-Ochoa, Andrea Alejandra (Zootaxa, 2020)
Pentamera fonsecae n. sp. is described from seven specimens as a new species of Thyonidae from the Pacific coast of Costa Rica. It is distinguished from its congeners by having tables with ladder-shaped spires in the body wall, and tube feet with curved support tables of variable height and tables as those found in the body wall slightly smaller than those from the body wall. This species is distributed in Guanacaste, Costa Rica, from 28.5 to 40 m on muddy bottoms.